Combined soft tissue plastics in treatment of the leg infected necrotic lesions - Bets, Iryna; Vyrva, Oleg; Bets, Grygorii (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Anatomical features of the leg create prerequisites for the occurrence of severe damage to bone-soft structures with the further development of infection-necrotic complications and osteoielitus. A difficult problem is the development of infected soft tissue defects. Objective. To study the effectiveness of the use of plastic surgical technologies using skin-fascial and muscular patches based on angiosomal concept by Taylor & Palmer. Methods. Treatment results analysis of 3 patients with necrotic defects of the leg soft tissues. All patients initially received high-energy different sites fractures of the leg bones and they were given metaloostheosynthesis using plates. In all cases, treatment was complicated by the occurrence of trophic disorders with infected full-layer defects of soft tissues that did not heal. Results. According to the angiosomal Taylor’s & Palmer’s theory, the human body is divided into 40 three-dimensional zones that combine skin with subordinate fiber and muscles, and have clear limits of blood supply to one nourishing artery. Full-haired soft-blooded patches, taking into account areas of angiosomes, are supplied throughout the plane and to the full depth, which guarantees much better results at the transplant site. The use of traditional plastics technologies in study group patients, on previous treatment did not lead to positive results, and the use of combined plastics based on the angiosomes concept allowed to obtain 100 % positive results, with complete healing of the foci of infection and the absence of relapses. Conclusions. A new stage in the development of plastic surgery, based on the angiosomes theory of human body structure by the blood supply to Taylor & Palmer, is promising for use in traumatology orthopaedics. The experience of using angiosomal patches for plastics of infected defects of the leg soft tissues has proved the high efficiency of this technology, which confirms the expediency of continuing research into the angiosomal theory in the treatment of such pathology another sites. Retrospective analysis of the etiology and pathogenesis for the leg tissues post-traumatic infected defects can be used to correct fracture treatment tactics in order to avoid the development of such complications.